ANALISIS PENGUNAAN MODAL KERJA PADA PT. PRAGA ANUGRAH NUSANTARA DI BONTANG - Elfreda Aplonia Lau., Nirlin veronika LCA Robin Jonathan (EKONOMIA, 2017)
Working capital is the wealth or assets required by the company to conduct activities or operational activities of the company. This shows that the rotation of the capital obtained both inside and outside the company is required to be managed as effectively as possible.The purpose of this study is to determine whether or not the use of working capital at PT. Praga Anugrah Nusantara in view of the cash turnover, inventory turnover and working capital turnover. The basic theory used is the management accounting by using the ratio analysis tool Working capital turn Over.The results showed:Cash turnover from 2013 to 2014 decreased by  55,09 % and from 2014 to 2015 decreased by  41.75% so it can be said that the use of working capital at PT. Praga Anugrah Nusantara in 2015 is not effective, when compared with the cash turnover in 2014 and 2013, thus the hypothesis of this study that the use of working capital of PT. Praga Anugrah Nusantara in 2015 is ineffective compared to 2013 and 2014, accepted.Inventory turnover from 2013 to 2014 by 0% and from 2104 to 2015 decreased by  46.99% so it can be said that the use of working capital at            PT. Praga Anugrah Nusantara in 2015 is not effective, when compared with the use of working capital in 2014 and 2013, thus the hypothesis of this study that the use of working capital of PT. Praga Anugrah Nusantara in 2015 is ineffective compared to 2013 and 2014, accepted.Working capital turnover from 2013 to 2014 decreased by  64.41% and from 2104 to 2015 decreased by  32.23% so it can be said that the use of working capital at PT. Praga Anugrah Nusantara in 2015 is not effective, when compared with the use of working capital in 2014 and 2013, thus the hypothesis of this study that the use of working capital of PT. Praga Anugrah Nusantara in 2015 is ineffective compared to 2013 and 2014, accepted